Payday lending : global growth of the high-cost credit market - Packman, Carl; SpringerLink (Online service). (New York : Palgrave Macmillan US, 2014)
Payday Lending looks at the growth of the high cost credit industry from the early payday lending industry in the early 1990s to its development in the US as a highly profitable industry around the world.
Keywords: Loans, Personal; Consumer credit; Bookkeeping; Business enterprises -- Finance